Development of an Improved Rhodium Catalyst for Z‐Selective Anti‐Markovnikov Addition of Carboxylic Acids to Terminal Alkynes. Issue 36 (22nd July 2013) - Wei, Siping; Pedroni, Julia; Meißner, Antje; Lumbroso, Alexandre; Drexler, Hans‐Joachim; Heller, Detlef; Breit, Bernhard
Abstract To develop more active catalysts for the rhodium‐catalyzed addition of carboxylic acids to terminal alkynes furnishing anti‐Markovnikov Z enol esters, a thorough study of the rhodium complexes involved was performed. A number of rhodium complexes were characterized by NMR, ESI‐MS, and X‐ray analysis and applied as catalysts for the title reaction. The systematic investigations revealed that the presence of chloride ions decreased the catalyst activity. Conversely, generating and applying a mixture of two rhodium species, namely, [Rh(DPPMP)2][H(benzoate)2] (DPPMP=diphenylphosphinomethylpyridine) and [Rh(COD)(μ2‐benzoate)2], provided a significantly more active catalyst. Furthermore, the addition of a catalytic amount of base (Cs2CO3) had an additional accelerating effect. This higher catalyst activity allowed the reaction time to be reduced from 16 to 1–4 h while maintaining high selectivity. Studies on the substrate scope revealed that the new catalysts have greater functional‐group compatibility.